Job satisfaction : from assessment to intervention - Spector, Paul E. (Routledge, 2022)
"Distilling the vast literature on this most frequently studied variable in organizational behavior, Paul E. Spector provides students and professionals with a pithy overview of the research and application of job satisfaction. In addition to discussing the nature of and techniques for assessing job satisfaction, this text summarizes the findings regarding how people feel towards work, including cultural and gender differences in job satisfaction, personal and organizational antecedents, potential consequences, and interventions to improve job satisfaction. Students, researchers and practitioners will particularly appreciate the extensive list of references and the Job Satisfaction Survey included in the Appendix. This book includes the latest research and new topics including the business case for job satisfaction, customer service, disabled workers, leadership, mental health, organizational climate, virtual work, and work-family issues. Further, paulspector.com features an ongoing series of blog articles, links to assessments mentioned in the book, and other resources on job satisfaction to coincide with this text. This book is ideal for professionals, researchers, and undergraduate and graduate students in industrial and organizational psychology and organizational behavior, as well as in specialized courses on job attitudes or job satisfaction"--